A Detailed Technical Analysis of a Microservices Architecture Conceptual Model:Rationale, Operation, and Implementation - Andiani (Utilitas Mathematica, 2025)
Microservices architectures have emerged as a primary method for building scalable, resilient, and modular systems that demand high performance and continuous evolution. Although significant effort has been invested in discussing the benefits of microservices, practitioners still face notable obstacles, including orchestrating services across hybrid or edge environments, modeling cross-domain workflows, and ensuring robust domain-driven design. The present article introduces a comprehensive conceptual diagram to illustrate the fundamental components of a microservices ecosystem, grounded in the latest research on cloud-edge orchestration (Roda-Sanchez et al., 2023), event-driven and domain-driven design (Myllynen et al., 2023), hybrid cloud migration (Beeraka, 2025), and automated microservice deployments (Zúñiga-Prieto et al., 2017). The discussion covers each architectural component’s technical rationale, typical operation, and strategies for implementation, with reference to advanced topics such as data fusion for observability (Tzanettis et al., 2022), pattern-based integration (Yussupov et al., 2020), and fault tolerance enhancements (Rasheedh et al., 2024). A simulated e-commerce system further validates the proposed model by showcasing real-world performance, load scenarios, and the pitfalls of partial failures. The article concludes with a consideration of future directions, including the role of eBPF-based service mesh solutions (Sedghpour et al., 2022) and data-driven orchestration approaches (Bacchiani et al., 2021; Bergami, 2024).